Enhanced thrust performance of a two dimensional elliptic airfoil at high flapping frequency in a forward flight. (January 2018) - Dash, S.M.; Lua, K.B.; Lim, T.T.; Yeo, K.S.
Abstract: This study is motivated by our earlier investigation Lua et al. (2016) which shows that a two-dimensional elliptic airfoil undergoing sinusoidal flapping motion experiences thrust deterioration when the flapping frequency exceeds a certain critical value (or critical Strouhal number, St c r ). To alleviate this unfavorable thrust generation condition, we propose two novel effective angle of attack profiles, namely smooth trapezoid (STEA) profile and elliptic trapezoid (ETEA) profile. These profiles are designed to ensure that the airfoil still experiences the same effective angle of attack amplitude as the sinusoidal flapping while concurrently reducing the detrimental effect of high rotation rate. The effectiveness of these two proposed profiles is confirmed by our numerical and experimental studies. In particular, our results show that at low to moderate flapping frequency, thrust generation is almost invariant to the type of angle of attack profiles applied, but at high flapping frequency ( S t > St c r ), the proposed profiles produce higher thrust than the sinusoidal flapping. The thrust augmentation can be attributed to the suppression of the adverse low pressure region in the vicinity of the airfoil, which is a consequence of the reduced rotation rate. Of the two proposed profiles, the ETEA with its steep acceleration phase produces a higher time-average thrust than the STEA near the stroke reversal. Also, in line with our previous finding, thrust augmentation for both STEA and ETEA is a function of the base length of the trapezoid, with a broader one producing a better thrust performance.